Sexual partner selection and HIV risk reduction among Black and White men who have sex with men. - Eaton, Lisa A; Kalichman, Seth C; Cherry, Chauncey (American journal of public health, 2010)
We examined differences in sexual partner selection between Black and White men who have sex with men (MSM) to better understand how HIV status of participants' sexual partners and related psychosocial measures influence risk taking among these men.
Keywords: Adult; African Americans; Attitude to Health; Choice Behavior; Cross-Cultural Comparison; Cross-Sectional Studies; European Continental Ancestry Group; Georgia; Health Knowledge, Attitudes, Practice; Health Status Disparities; HIV Infections; Homosexuality, Male; Humans; Logistic Models; Male; Motivation; Multivariate Analysis; Questionnaires; Risk Reduction Behavior; Sexual Partners; Unsafe Sex